ENGEMBANGAN KOMPETENSI APARATUR SIPIL NEGARA DI DINAS PENDIDIKAN KABUPATEN INTAN JAYA PROPINSI PAPUA - SANI, TITUS; RARES, JOYCE JACINTA; OGOTAN, MARTHA (Sam Ratulangi University, 2017)
Abstract: This study aims to determine the development of the competence of the State Civil Apparatus inthe Education Office of Intan Jaya Regency. By using quantitative methods Informant research consists of: head ofservice, secretary of service, heads of fields, heads of sections, sub heads, and staff / executives; all amounted toseven civil State Apparatus (ASN). Based on the results of the research: (1) Development of ASN competence inDinasPendidikan Kabupaten Intan Jaya is done by involving employees in education and training, namelyStructural Training / Poverty / PIM and Technical / Functional Training, but can’t be realized or realized optimally.(2) The development of ASN competencies The Intan Jaya District Education Office is also programmed throughparticipation in courses, upgrading, as well as seminars and workshops, but this program has not been optimallyrealized. (3) The development of ASN/competence of Dinas Pendidikan is also conducted through workplacetraining, especially rotation of job that is shifting or transferring of employee from another job/position/job within acertain period of time within the Education Office.So this study recommended some things as follows: (1) Training needs to be increased by allocating alarger budget and adequate, as well as increased provision of facilities Diklat. (2) Technical Training should bemore widely implemented for ASN to develop the competence of knowledge and technical skills directly related tothe main duties of the employees.Keywords: Competence Development, State Civil Apparatus (ASN)